Voices of contention: the value of development narratives in the age of climate (change) migration misconceptions - Santos, Claudia (2021)
This paper offers a fresh perspective on the predominant narrative that links climate change to migration. We review how this narrative is being used to promote securitization policies and to limit migration avenues. We propose a reinterpretation of this connection by drawing on its current critique and acknowledging the alternative conclusions that emerge from local perceptions of climate change. We explore human development perspectives to demonstrate how context-specific power structures and the politics behind the causes of (non-)migration, inhibit the freedom of choice by individuals and households over possible migratory decisions under changing climate threats and dangers. To achieve the well-being and social justice necessary for individuals to cope with the conditions of (non-)climate change, we conclude that current development aspirations must shift focus from human capital to human capability